Upaya Guru dalam Meningkatkan Keterampilan Membaca pada Pembelajaran Pandemi di Kelas Rendah - Welly Priaga; Edi Siswanto (Jurnal Gentala Pendidikan Dasar, 2022)
This study intends to explore more deeply according to the conditions that occur and describe the efforts of teachers in improving the reading skills of low-grade students during the Covid-19 pandemic. This research was conducted at SDN 19 Pangkalpinang. The time used in the study was carried out for 4 months, namely from September to December of the 2021/2022 school year. There are two research subjects, namely, one class II A teacher and also class II A students at SDN 19 Pangkalpinang which has a total of 37 students. The data techniques in this study were observation, semi-structured interviews, and documentation. The results of the study are that teachers have their own efforts so that they have increased which researchers conclude as 6M efforts, as follows: 1). Categorize, 2). Video, 3). Motivating, 4). Teaching with the SAS Method, 5). Visiting, 6). Collaborating with parents, this makes a significant improvement to students' reading skills.